2015
DOI: 10.3733/ca.v069n03p142
|View full text |Cite
|
Sign up to set email alerts
|

Forest biomass diversion in the Sierra Nevada: Energy, economics and emissions

Abstract: As an alternative to open pile burning, use of forest wastes from fuel hazard reduction projects at Blodgett Forest Research Station for electricity production was shown to produce energy and emission benefits: energy (diesel fuel) expended for processing and transport was 2.5% of the biomass fuel (energy equivalent); based on measurements from a large pile burn, air emissions reductions were 98%-99% for PM 2.5 , CO (carbon monoxide), NMOC (nonmethane organic compounds), CH 4 (methane) and BC (black carbon), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…With respect to other results derived from the Blodgett Project, it was demonstrated that 248 utilization of biomass from these large debris piles can result in energy and air quality benefits [20],…”
mentioning
confidence: 84%
“…With respect to other results derived from the Blodgett Project, it was demonstrated that 248 utilization of biomass from these large debris piles can result in energy and air quality benefits [20],…”
mentioning
confidence: 84%
“…With respect to other results derived from the Blodgett Project, it was demonstrated that utilization of biomass from these large debris piles can result in energy and air quality benefits [23], as follows:…”
Section: Discussionmentioning
confidence: 99%
“…The overall sizes of the piles generated were typical of thinning operations in young and mature forests, with the bulk volume averaging 1784 m 3 per pile [23]. At each BFRS slash pile, a grapple excavator was used to transfer the waste material into a horizontal grinder.…”
Section: Study Site and Treatmentmentioning
confidence: 99%
“…In addition, leaving large piles of forest residues near houses or within public parks have been a concern due to high risk of fire hazard and other forest management issues (i.e., growing and rehabilitation). For this reason, open pile burning (OPB) has been widely used in the Western U.S. to dispose of forest residues, to reduce wildfire hazard, and improve forest and productivity [7,8]. This forest residues disposal method has been extensively used as it provides a cost-effective option for disposal of forest residues [9,10].…”
Section: Introductionmentioning
confidence: 99%